Breach of Contract and its Remedies; Theory and Practice with Special References to Nepalese Law - Giri, Saroj Kumar (Journal of Management, 2024)
This research provides a thorough examination of breach of contract concepts and remedies, focusing on their application within Nepal's legal framework. It begins with a comprehensive overview of contract fundamentals and various breach types—minor, material, anticipatory, and actual—clarifying their legal implications. Legal remedies such as compensatory damages, consequential damages, specific performance, injunctions, rescission, and liquidated damages are detailed, emphasizing their legal basis and practical implications. Principal challenges in enforcing contract law in Nepal are identified, with integration of international guidelines from UNIDROIT Principles, CISG, and PECL providing a global perspective. The Nepalese Civil Code 2074 and earlier contract acts are referenced for historical context, while international case law examples illustrate their impact on Nepal's legal system. Notable Nepalese judicial decisions underscore the Supreme Court's role in interpreting and enforcing contract law, striving to align practices with international standards. Employing doctrinal research methods, the article highlights the progressive evolution of contract breach remedies in Nepal. Despite existing gaps, the judiciary actively addresses shortcomings to enhance legal consistency and align practices globally. This evolving landscape reflects Nepal's commitment to justice and a reliable legal environment for domestic and international commerce. The analysis enriches understanding of theoretical foundations and practical applications of Nepalese contract law, particularly concerning breach of contract and associated remedies.